A magnesium-zinc ferrite material and its preparation method and application

By adding specific component proportions and auxiliary components, magnesium-zinc ferrite materials with high temperature stability, strength, resistivity and moderate magnetic permeability are prepared, which solves the problem of insufficient performance of existing materials and is suitable for the preparation of inductors and large-scale industrial production.

CN119219404BActive Publication Date: 2025-04-04BIAOQI MAGNETOELECTRIC PROD (FOGANG) CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411264236.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-04-04
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing magnesium-zinc ferrite materials have problems such as poor temperature stability, low strength, and low resistivity, which are difficult to fully meet the practical application requirements.

Method used

Magnesium-zinc ferrite materials composed of specific mole percent components, including main components such as Fe2O3, MgO, ZnO, CuO, etc., and auxiliary components such as CaCO3, SiO2, Co2O3, SrCO3 or BaCO3, V2O5, ZrO2 and Al2O3 are added, and prepared by wet ball milling, spray granulation, prefixing, crushing, pressing molding, sintering and annealing.

Benefits of technology

It improves the temperature stability, strength, resistivity and magnetic permeability of magnesium-zinc ferrite materials, and is suitable for the preparation of inductors. It has simple preparation methods, wide sources of raw materials, and low production costs. It is suitable for large-scale industrial production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005036687180000091
    Figure BDA0005036687180000091
Patent Text Reader

Abstract

The present invention discloses a magnesium-zinc ferrite material and a preparation method and application thereof. The magnesium-zinc ferrite material of the present invention is composed of a main component and an auxiliary component. The main component includes Fe 2 O 3 , MgO, ZnO and CuO, and auxiliary components include CaCO 3 、SiO 2 、Co 2 O 3 、SrCO 3 or / and BaCO 3 、V 2 O 5 、ZrO 2 and Al 2 O 3 . The preparation method of the magnesium-zinc ferrite material of the present invention comprises the following steps: 1) pre-sintering to prepare main component particles; 2) preparing the main component particles, auxiliary components and binder into granular materials; 3) injecting the granular materials into a mold for compression molding, and then sintering and annealing. The magnesium-zinc ferrite material of the present invention has the advantages of high temperature stability, high strength, high resistivity, moderate magnetic permeability, etc., and can be used to prepare inductors. The preparation method is simple, the raw material source is wide, the production cost is low, and it is suitable for large-scale industrial production and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of soft magnetic materials, and in particular to a magnesium-zinc ferrite material and a preparation method and application thereof. Background Art

[0002] Nickel-zinc ferrite has the characteristics of high frequency, wide frequency, high impedance, and low loss, and is a widely used soft ferrite material. However, the price of NiO is relatively high, and the price is still rising, which has caused the continuous increase in the manufacturing cost of nickel-zinc ferrite (NiO accounts for a large proportion of nickel-zinc ferrite, and the increase in NiO price will directly affect the manufacturing cost of nickel-zinc ferrite), which seriously restricts the further expansion of the application of nickel-zinc ferrite.

[0003] As we all know, the price of MgO is much lower than that of NiO (MgO is only about 1 / 50 of NiO), so the manufacturing cost of Mg-Zn ferrite is lower than that of Ni-Zn ferrite. Moreover, the performance of Mg-Zn ferrite in many aspects is not much different from that of Ni-Zn ferrite, and it can completely replace Ni-Zn ferrite to a certain extent. However, the existing Mg-Zn ferrite generally has problems such as poor temperature stability, low strength, and low resistivity, and it is still difficult to fully meet the requirements of practical applications.

[0004] Therefore, it is of great significance to develop a magnesium-zinc ferrite material with high temperature stability, high strength, high resistivity and moderate magnetic permeability.

[0005] The above statements merely provide background information related to the present invention and do not necessarily constitute prior art. Summary of the invention

[0006] The purpose of the present invention is to provide a magnesium-zinc ferrite material and a preparation method and application thereof.

[0007] The technical solution adopted by the present invention is:

[0008] A magnesium-zinc ferrite material consists of a main component and an auxiliary component; the main component includes the following components in molar percentage: Fe2O3: 47% to 50%; MgO: 18% to 24%; ZnO: 18% to 24%; CuO: 5% to 8%; the composition of the auxiliary component and the mass percentage of the auxiliary component to the main component are as follows: CaCO3: 0.05% to 0.15%; SiO2: 0.02% to 0.10%; Co2O3: 0.03% to 0.07%; SrCO3 or / and BaCO3: 0.05% to 0.15%; V2O5: 0.03% to 0.07%; ZrO2: 0.03% to 0.07%; Al2O3: 0.03% to 0.07%.

[0009] A method for preparing the magnesium-zinc ferrite material as described above comprises the following steps:

[0010] 1) mixing the components of the main component, wet ball milling, spray granulation, pre-calcination and crushing to obtain the main component particles;

[0011] 2) mixing the main component particles, the auxiliary components and the binder, performing wet ball milling, and then spray granulating to obtain granular materials;

[0012] 3) The granular material is injected into a mold for compression molding, and then sintered and annealed to obtain the magnesium-zinc ferrite material.

[0013] Preferably, the process parameters of the wet ball milling in step 1) are as follows: the ball milling medium is water, the mass ratio of solid material, ZrO2 balls and water is 1:1.8-2.2:1.0-1.5, and the ball milling time is 1h-3h.

[0014] Preferably, the spray granulation in step 1) is carried out at a temperature of 190° C. to 220° C. and a pressure of 2 MPa to 3 MPa.

[0015] Preferably, the pre-firing in step 1) is carried out in an air atmosphere, the pre-firing temperature is 850° C. to 950° C., and the pre-firing time is 2 h to 4 h.

[0016] Further preferably, the specific operation of the pre-firing in step 1) includes: controlling the heating rate to be 3°C / min-7°C / min in an air atmosphere to heat from room temperature to 850°C-950°C and then keeping the temperature for 2h-4h.

[0017] Preferably, in step 1), the D of the main component particles 50 The particle size is 1μm~5μm.

[0018] Preferably, the binder in step 2) is at least one of polyvinyl alcohol, polyvinyl pyrrolidone and polyvinyl butyral.

[0019] Preferably, the amount of the binder in step 2) is 0.8% to 1.5% of the total mass of the main component and the auxiliary component.

[0020] Preferably, the process parameters of the wet ball milling in step 2) are as follows: the ball milling medium is water, the mass ratio of solid material, ZrO2 balls and water is 1:1.8-2.2:1.8-2.5, and the ball milling time is 2h-4h.

[0021] Preferably, the spray granulation in step 2) is carried out at a temperature of 230° C. to 280° C. and a pressure of 3 MPa to 4 MPa.

[0022] Preferably, in step 2), the D of the granular material 50 The particle size is 8μm~15μm.

[0023] Preferably, the compression molding in step 3) is carried out at a pressure of 40 MPa to 80 MPa, and the holding time is 3 min to 10 min.

[0024] Preferably, the density of the green body obtained by compression molding in step 3) is 2.8 g / cm 3 ~3.5g / cm 3 .

[0025] Preferably, the sintering in step 3) is carried out in an air atmosphere, the sintering temperature is 1100° C. to 1200° C., and the sintering time is 2 h to 4 h.

[0026] Further preferably, the specific operation of sintering in step 3) includes: controlling the heating rate to be 2°C / min-5°C / min in an air atmosphere, heating from room temperature to 1100°C-1200°C and then keeping the temperature for 2h-4h.

[0027] Preferably, the annealing in step 3) is carried out at a temperature of 400° C. to 500° C., and the annealing time is 20 min to 40 min.

[0028] An inductor comprises the above-mentioned magnesium-zinc ferrite material.

[0029] An electronic product comprises the inductor.

[0030] The beneficial effects of the present invention are as follows: the magnesium-zinc ferrite material of the present invention has the advantages of high temperature stability, high strength, high resistivity, moderate magnetic permeability, etc., can be used to prepare inductors, and its preparation method is simple, the raw material source is wide, the production cost is low, and it is suitable for large-scale industrial production and application.

[0031] Specifically:

[0032] 1) CaCO3 and SiO2 are added to the magnesium-zinc ferrite material of the present invention. CaCO3 and SiO2 can form calcium silicate in the grain boundary to increase the resistivity of the grain boundary, thereby improving the resistivity of the magnesium-zinc ferrite material, and also improving the temperature stability and Q value of the magnesium-zinc ferrite material to a certain extent;

[0033] 2) Co2O3 is added to the magnesium-zinc ferrite material of the present invention. Although Co2O3 has a certain effect on the magnetic permeability of the magnesium-zinc ferrite material, it can greatly improve the Q value of the magnesium-zinc ferrite material and reduce the temperature coefficient of the magnesium-zinc ferrite material, so that the magnesium-zinc ferrite material can maintain the stability of the initial magnetic permeability and Q value characteristics within a wider temperature range;

[0034] 3) SrCO3 and / or BaCO3 are added to the magnesium-zinc ferrite material of the present invention, which can refine the grains, thereby increasing the anisotropy of the magnesium-zinc ferrite material, improving the cutoff frequency, and also greatly improving the resistivity of the magnesium-zinc ferrite material;

[0035] 4) V2O5, ZrO2 and Al2O3 are added to the magnesium-zinc ferrite material of the present invention. The synergistic effect of these three components can greatly improve the strength of the magnesium-zinc ferrite material, and can also effectively reduce the sintering temperature of the magnesium-zinc ferrite material, refine the grains, and thus effectively reduce the loss of the magnesium-zinc ferrite material;

[0036] 5) The present invention further performs annealing on the green body pressed from the granular material after sintering. The annealing operation can refine the grain size and make the grain size more uniform, thereby effectively improving the strength, magnetic permeability and other properties of the magnesium-zinc ferrite material;

[0037] 6) The preparation method of the magnesium-zinc ferrite material of the present invention is simple, the raw material source is wide, the production cost is low, and no special production equipment is required, so it is suitable for large-scale industrial production and application. DETAILED DESCRIPTION

[0038] The present invention will be further explained and illustrated below in conjunction with specific embodiments.

[0039] Embodiment 1:

[0040] A magnesium-zinc ferrite material, the preparation method of which is as follows:

[0041] 1) Fe2O3 powder, MgO powder, ZnO powder and CuO powder were added to a ball mill as main components, and the molar percentage of each component in the main component was: Fe2O3: 48.5%; MgO: 22%; ZnO: 22.5%; CuO: 7%. ZrO2 balls with a diameter of 3 mm to 5 mm and water were added and ball milled for 2.5 hours. The mass ratio of solid material, ZrO2 balls and water was 1:2:1.2. The obtained slurry was transferred to a spray granulator and spray granulated at a temperature of 200°C and a pressure of 2.5 MPa. The obtained particles were placed in an air atmosphere and heated at a rate of 5°C / min from room temperature to 900°C and kept warm for 2 hours. The material was then transferred to a pulverizer for pulverization to obtain main component particles (D 50 Particle size is 1.1 μm);

[0042] 2) Adding the main component particles, auxiliary components and polyvinyl alcohol (number average molecular weight of 50,000) into a ball mill, the auxiliary components are composed of CaCO3 powder, SiO2 powder, Co2O3 powder, BaCO3 powder, V2O5 powder, ZrO2 powder and Al2O3 powder, and the mass percentage of the auxiliary components to the main components is as follows: CaCO3: 0.15%; SiO2: 0.08%; Co2O3: 0.05%; BaCO3: 0.10%; V2O5: 0.05%; ZrO2: 0.05%; Al2O3: 0.05%, the amount of polyvinyl alcohol is 1.5% of the total mass of the main component and the auxiliary component, and then ZrO2 balls with a diameter of 3mm to 5mm and water are added and ball milled for 3h. The mass ratio of solid material, ZrO2 balls and water is 1:2:2. The obtained slurry is then transferred to a spray granulator and spray granulated at a temperature of 250°C and a pressure of 3.5MPa to obtain a granular material (D 50 Particle size is 8.7 μm);

[0043] 3) The pellets were injected into the mold and then maintained at a pressure of 50 MPa for 5 min to form a green body (ring-shaped, with an outer diameter of 25 mm, an inner diameter of 15 mm, a thickness of 6 mm, and a density of 3.0 g / cm 3 ), then control the heating rate to be 2.5℃ / min in air atmosphere to heat from room temperature to 1120℃ and keep it for 2h, then cool to 450℃ and keep it for 30min, and then naturally cool to room temperature to obtain magnesium-zinc ferrite material (magnetic ring).

[0044] Embodiment 2:

[0045] A magnesium-zinc ferrite material, the preparation method of which is as follows:

[0046] 1) Fe2O3 powder, MgO powder, ZnO powder and CuO powder are added to a ball mill as main components, and the molar percentage of each component in the main component is: Fe2O3: 49%; MgO: 21%; ZnO: 23%; CuO: 7%. ZrO2 balls with a diameter of 3mm to 5mm and water are then added and ball milled for 2h. The mass ratio of solid material, ZrO2 balls and water is 1:2:1. The obtained slurry is then transferred to a spray granulator for spray granulation at a temperature of 200°C and a pressure of 2MPa. The obtained particles are then placed in an air atmosphere and heated from room temperature to 900°C at a controlled heating rate of 5°C / min, and then kept warm for 2h. The material is then transferred to a pulverizer for pulverization to obtain main component particles (D 50 Particle size is 1.4 μm);

[0047] 2) Adding the main component particles, auxiliary components and polyvinyl alcohol (number average molecular weight of 50,000) into a ball mill, the auxiliary components are composed of CaCO3 powder, SiO2 powder, Co2O3 powder, BaCO3 powder, V2O5 powder, ZrO2 powder and Al2O3 powder, and the mass percentage of the auxiliary components to the main components is as follows: CaCO3: 0.15%; SiO2: 0.08%; Co2O3: 0.05%; BaCO3: 0.10%; V2O5: 0.05%; ZrO2: 0.05%; Al2O3: 0.05%, the amount of polyvinyl alcohol is 1.2% of the total mass of the main component and the auxiliary component, and then ZrO2 balls with a diameter of 3mm to 5mm and water are added and ball milled for 3h. The mass ratio of solid material, ZrO2 balls and water is 1:2:2. The obtained slurry is then transferred to a spray granulator and spray granulated at a temperature of 250°C and a pressure of 3.5MPa to obtain a granular material (D 50 Particle size is 10.5 μm);

[0048] 3) The pellets were injected into the mold and then maintained at a pressure of 50 MPa for 5 min to form a green body (ring-shaped, with an outer diameter of 25 mm, an inner diameter of 15 mm, a thickness of 6 mm, and a density of 3.1 g / cm 3 ), then control the heating rate to be 2.5℃ / min in air atmosphere to heat from room temperature to 1120℃ and keep it for 2h, then cool to 450℃ and keep it for 30min, and then naturally cool to room temperature to obtain magnesium-zinc ferrite material (magnetic ring).

[0049] Embodiment 3:

[0050] A magnesium-zinc ferrite material, the preparation method of which is as follows:

[0051] 1) Fe2O3 powder, MgO powder, ZnO powder and CuO powder are added to a ball mill as main components, and the molar percentage of each component in the main component is: Fe2O3: 48.5%; MgO: 24%; ZnO: 20.5%; CuO: 7%. ZrO2 balls with a diameter of 3mm to 5mm and water are added and ball milled for 2h. The mass ratio of solid material, ZrO2 balls and water is 1:2:1. The obtained slurry is then transferred to a spray granulator for spray granulation at a temperature of 200°C and a pressure of 2MPa. The obtained particles are then placed in an air atmosphere and heated at a rate of 5°C / min from room temperature to 900°C and kept warm for 2h. The material is then transferred to a pulverizer for pulverization to obtain main component particles (D 50 Particle size is 1.3 μm);

[0052] 2) Adding the main component particles, auxiliary components and polyvinyl alcohol (number average molecular weight of 50,000) into a ball mill, the auxiliary components are composed of CaCO3 powder, SiO2 powder, Co2O3 powder, SrCO3 powder, V2O5 powder, ZrO2 powder and Al2O3 powder, and the mass percentage of the auxiliary components to the main components is as follows: CaCO3: 0.12%; SiO2: 0.06%; Co2O3: 0.05%; SrCO3: 0.10%; V2O5: 0.05%; ZrO2: 0.06%; Al2O3: 0.05%, the amount of polyvinyl alcohol is 0.8% of the total mass of the main component and the auxiliary component, and then ZrO2 balls with a diameter of 3mm to 5mm and water are added and ball milled for 3h. The mass ratio of solid material, ZrO2 balls and water is 1:2:2. The obtained slurry is then transferred to a spray granulator and spray granulated at a temperature of 250°C and a pressure of 3.5MPa to obtain a granular material (D 50 Particle size is 9.5 μm);

[0053] 3) The pellets were injected into the mold, and then maintained at a pressure of 50 MPa for 5 min to form a green body (ring-shaped, with an outer diameter of 25 mm, an inner diameter of 15 mm, a thickness of 6 mm, and a density of 3.2 g / cm 3 ), then control the heating rate to be 2.5℃ / min in air atmosphere to heat from room temperature to 1150℃ and keep it for 2h, then cool to 480℃ and keep it for 20min, and then naturally cool to room temperature to obtain magnesium-zinc ferrite material (magnetic ring).

[0054] Embodiment 4:

[0055] A magnesium-zinc ferrite material, the preparation method of which is as follows:

[0056] 1) Fe2O3 powder, MgO powder, ZnO powder and CuO powder are added to a ball mill as main components, and the molar percentage of each component in the main component is: Fe2O3: 48.5%; MgO: 22%; ZnO: 22.5%; CuO: 7%. ZrO2 balls with a diameter of 3mm to 5mm and water are added and ball milled for 2h. The mass ratio of solid material, ZrO2 balls and water is 1:2:1. The obtained slurry is then transferred to a spray granulator for spray granulation at a temperature of 200°C and a pressure of 2MPa. The obtained particles are then placed in an air atmosphere and heated from room temperature to 900°C at a controlled heating rate of 5°C / min and then kept warm for 2h. The material is then transferred to a pulverizer for pulverization to obtain main component particles (D 50 Particle size is 1.3 μm);

[0057] 2) Adding the main component particles, auxiliary components and polyvinyl alcohol (number average molecular weight of 50,000) into a ball mill, the auxiliary components are composed of CaCO3 powder, SiO2 powder, Co2O3 powder, BaCO3 powder, V2O5 powder, ZrO2 powder and Al2O3 powder, and the mass percentage of the auxiliary components to the main components is as follows: CaCO3: 0.15%; SiO2: 0.08%; Co2O3: 0.05%; BaCO3: 0.10% ; V2O5: 0.05%; ZrO2: 0.05%; Al2O3: 0.05%, the amount of polyvinyl alcohol is 1% of the total mass of the main component and the auxiliary component, and then ZrO2 balls with a diameter of 3mm to 5mm and water are added and ball milled for 3h. The mass ratio of solid material, ZrO2 balls and water is 1:2:2. The obtained slurry is then transferred to a spray granulator and spray granulated at a temperature of 250°C and a pressure of 3.5MPa to obtain a granular material (D 50 Particle size is 9.2 μm);

[0058] 3) The pellets were injected into the mold, and then maintained at a pressure of 50 MPa for 5 min to form a green body (ring-shaped, with an outer diameter of 25 mm, an inner diameter of 15 mm, a thickness of 6 mm, and a density of 3.2 g / cm 3 ), then control the heating rate to be 2.5℃ / min in air atmosphere to heat from room temperature to 1120℃ and keep it for 2h, then cool to 450℃ and keep it for 30min, and then naturally cool to room temperature to obtain magnesium-zinc ferrite material (magnetic ring).

[0059] Comparative Example 1:

[0060] A magnesium-zinc ferrite material (magnetic ring) is completely the same as Example 4 except that no auxiliary components are used during preparation.

[0061] Comparative Example 2:

[0062] A magnesium-zinc ferrite material (magnetic ring) is completely the same as Example 4 except that the auxiliary components used in the preparation do not contain CaCO3 and SiO2.

[0063] Comparative Example 3:

[0064] A magnesium-zinc ferrite material (magnetic ring) is completely the same as Example 4 except that the auxiliary component used in the preparation does not contain Co2O3.

[0065] Comparative Example 4:

[0066] A magnesium-zinc ferrite material (magnetic ring) is completely the same as Example 4 except that the auxiliary component used in the preparation does not contain BaCO3.

[0067] Comparative Example 5:

[0068] A magnesium-zinc ferrite material (magnetic ring) is completely the same as Example 4 except that the auxiliary component used in the preparation does not contain V2O5.

[0069] Comparative Example 6:

[0070] A magnesium-zinc ferrite material (magnetic ring) is completely the same as Example 4 except that the auxiliary component used in the preparation does not contain ZrO2.

[0071] Comparative Example 7:

[0072] A magnesium-zinc ferrite material (magnetic ring) is completely the same as Example 4 except that the auxiliary component used in the preparation does not contain Al2O3.

[0073] Comparative Example 8:

[0074] A magnesium-zinc ferrite material (magnetic ring), except that no annealing treatment is performed in step 3) during preparation (i.e., it does not contain the operation of "cooling to 450° C. and then keeping warm for 30 minutes", and it is directly cooled naturally to room temperature after sintering). The rest is exactly the same as Example 4.

[0075] Performance Test:

[0076] 1) The performance test data of the magnesium-zinc ferrite materials in Examples 1 to 4 and Comparative Examples 1 to 8 are shown in the following table:

[0077] Table 1 Performance test data of magnesium zinc ferrite materials in Examples 1 to 4 and Comparative Examples 1 to 8

[0078] Test items <![CDATA[μ i ]]> Q Value Bs(mT) Resistivity (Ω·m) Bending strength(MPa) Example 1 646 42 392 <![CDATA[7.5×10 9 ]]> 92 Example 2 654 48 383 <![CDATA[8.1×10 9 ]]> 91 Example 3 642 45 388 <![CDATA[8.4×10 9 ]]> 92 Example 4 662 54 395 <![CDATA[9.0×10 9 ]]> 95 Comparative Example 1 673 28 310 <![CDATA[1.1×10 9 ]]> 54 Comparative Example 2 657 36 380 <![CDATA[5.5×10 9 ]]> 92 Comparative Example 3 668 30 372 <![CDATA[8.2×10 9 ]]> 88 Comparative Example 4 653 48 375 <![CDATA[3.4×10 9 ]]> 89 Comparative Example 5 655 45 383 <![CDATA[8.7×10 9 ]]> 62 Comparative Example 6 649 48 386 <![CDATA[8.4×10 9 ]]> 67 Comparative Example 7 654 47 388 <![CDATA[8.3×10 9 ]]> 66 Comparative Example 8 639 44 377 <![CDATA[8.1×10 9 ]]> 85

[0079] Note:

[0080] μ i (Initial magnetic permeability): The test was conducted using a precision electromagnetic analyzer 3260B, with the number of winding turns of the magnesium-zinc ferrite material (magnetic ring) being N=20Ts, the test temperature being 25°C, and the test frequency being 10MHz;

[0081] Q value: tested with impedance analyzer E4991, test frequency is 10MHz;

[0082] Bs (saturation magnetic flux density): tested using hysteresis loop analyzer SY8218, the number of winding turns of magnesium-zinc ferrite material (magnetic ring) is N=20Ts, the test temperature is 25°C, the test conditions are 1kHz, 1194A / m;

[0083] Resistivity: tested using a volume surface resistivity tester;

[0084] Bending strength: The size of the test specimen is 35mm×4mm×3mm. It is tested on a universal testing machine with a test span of 30mm and a displacement loading rate of 0.5mm / min.

[0085] From Table 1, we can see that:

[0086] a) The magnesium zinc ferrite materials in Examples 1 to 4 have moderate magnetic permeability, large Q value, large Bs, large resistivity, and large bending strength. The Q value, resistivity, and bending strength are significantly higher than those of the magnesium zinc ferrite material in Comparative Example 1 (without adding auxiliary components), and the Bs is also higher than that of the magnesium zinc ferrite material in Comparative Example 1, indicating that the addition of auxiliary components has little effect on the initial magnetic permeability of the magnesium zinc ferrite material, but can significantly improve the Q value, Bs, resistivity, and bending strength of the magnesium zinc ferrite material;

[0087] b) The Q value and resistivity of the magnesium-zinc ferrite material in Example 4 are significantly higher than those of the magnesium-zinc ferrite material in Comparative Example 2 (the auxiliary components do not contain CaCO3 and SiO2), and the Bs and bending strength are also larger, indicating that the addition of CaCO3 and SiO2 can significantly improve the Q value and resistivity of the magnesium-zinc ferrite material;

[0088] c) The Q value of the magnesium-zinc ferrite material in Example 4 is significantly higher than that of the magnesium-zinc ferrite material in Comparative Example 3 (the auxiliary component does not contain Co2O3), and the Bs, resistivity and bending strength are also larger, but the initial magnetic permeability is slightly lower, indicating that the addition of Co2O3 can significantly improve the Q value of the magnesium-zinc ferrite material, but at the same time it will have a certain impact on the initial magnetic permeability of the magnesium-zinc ferrite material;

[0089] d) The resistivity of the magnesium-zinc ferrite material in Example 4 is significantly higher than that of the magnesium-zinc ferrite material in Comparative Example 4 (the auxiliary component does not contain BaCO3), and the Q value, Bs and bending strength are also larger, indicating that the addition of BaCO3 can significantly improve the resistivity of the magnesium-zinc ferrite material;

[0090] e) The bending strength of the magnesium-zinc ferrite material in Example 4 is significantly higher than that of the magnesium-zinc ferrite materials in Comparative Examples 5 to 7 (the auxiliary components do not contain V2O5, ZrO2 or Al2O3), and the Q value, Bs and resistivity are also higher, indicating that only by adding V2O5, ZrO2 and Al2O3 at the same time can the strength of the magnesium-zinc ferrite material be significantly improved. Once any one of V2O5, ZrO2 and Al2O3 is missing, the effect of improving the strength of the magnesium-zinc ferrite material will be greatly reduced;

[0091] f) The Q value, Bs, resistivity and bending strength of the magnesium-zinc ferrite material in Example 4 are higher than those of the magnesium-zinc ferrite material in Comparative Example 8 (without annealing), indicating that annealing can refine the grain size and make the grain size more uniform, thereby effectively improving the initial magnetic permeability, Q value, mechanical strength and other properties of the magnesium-zinc ferrite material.

[0092] 2) Test the μ of the magnesium-zinc ferrite materials in Examples 1 to 4 at different temperatures i (initial magnetic permeability), the test results are shown in the following table:

[0093] Table 2 μ of magnesium zinc ferrite materials in Examples 1 to 4 at different temperatures i Test Results

[0094]

[0095]

[0096] It can be seen from Table 2 that the magnesium-zinc ferrite materials in Examples 1 to 4 can maintain a relatively stable initial magnetic permeability within a wide temperature range (-40°C to 120°C), have a wide temperature range of adaptability, and have very broad application prospects.

[0097] In summary, the magnesium-zinc ferrite material of the present invention has the advantages of high temperature stability, high strength, high resistivity, moderate magnetic permeability, etc., can be used to prepare inductors, and is suitable for large-scale industrial production and application.

[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A magnesium-zinc ferrite material, characterized in that: It is composed of a main component and an auxiliary component; the main component includes the following components in molar percentage: Fe2O3: 47% to 50%; MgO: 18% to 24%; ZnO: 18% to 24%; CuO: 5% to 8%; the composition and mass percentage of the auxiliary components to the main component are as follows: CaCO3: 0.05% to 0.15%; SiO2: 0.02% to 0.10%; Co2O3: 0.03% to 0.07%; SrCO3 or / and BaCO3: 0.05% to 0.15%; V2O5: 0.03% to 0.07%; ZrO2: 0.03% to 0.0 7%; Al2O3: 0.03%~0.07%; the magnesium-zinc ferrite material is made by a preparation method comprising the following steps: 1) mixing the components in the main component and performing wet ball milling, and then spray granulation, pre-calcining and crushing to obtain main component particles; 2) mixing the main component particles, auxiliary components and a binder and performing wet ball milling, and then spray granulation to obtain granular materials; 3) injecting the granular materials into a mold for compression molding, and then sintering and annealing to obtain the magnesium-zinc ferrite material; step 3) the annealing is carried out at a temperature of 400°C~500°C, and the annealing time is 20min~40min.

2. The magnesium-zinc ferrite material according to claim 1, characterized in that: The process parameters of the wet ball milling in step 1) are as follows: the ball milling medium is water, the mass ratio of solid material, ZrO2 balls and water is 1:1.8~2.2:1.0~1.5, and the ball milling time is 1h~3h; the spray granulation in step 1) is carried out at a temperature of 190℃~220℃ and a pressure of 2MPa~3MPa.

3. The magnesium-zinc ferrite material according to claim 1 or 2, characterized in that: Step 1) The pre-firing is carried out in an air atmosphere at a temperature of 850° C. to 950° C. and a pre-firing time of 2 h to 4 h.

4. The magnesium-zinc ferrite material according to claim 1, characterized in that: Step 2) The binder is at least one of polyvinyl alcohol, polyvinyl pyrrolidone and polyvinyl butyral; the amount of the binder in step 2) is 0.8% to 1.5% of the total mass of the main component and the auxiliary component.

5. The magnesium-zinc ferrite material according to claim 1 or 4, characterized in that: The process parameters of the wet ball milling in step 2) are as follows: the ball milling medium is water, the mass ratio of solid material, ZrO2 balls and water is 1:1.8~2.2:1.8~2.5, and the ball milling time is 2h~4h; the spray granulation in step 2) is carried out at a temperature of 230℃~280℃ and a pressure of 3MPa~4MPa.

6. The magnesium-zinc ferrite material according to claim 1, characterized in that: Step 3) The compression molding is carried out under a pressure of 40 MPa to 80 MPa, and the pressure holding time is 3 min to 10 min.

7. The magnesium-zinc ferrite material according to claim 1 or 6, characterized in that: Step 3) The sintering is carried out in an air atmosphere, the sintering temperature is 1100° C. to 1200° C., and the sintering time is 2 h to 4 h.

8. An inductor, characterized in that: The magnesium-zinc ferrite material comprises the magnesium-zinc ferrite material according to any one of claims 1 to 7.

9. An electronic product, characterized in that: The inductor according to claim 8 is included.

Citation Information

Patent Citations

  • Ultrahigh-frequency high-permeability low-loss manganese-zinc soft magnetic ferrite and preparation method thereof

    CN113563062A

  • Ferrite cemented body

    CN1294098A